(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
The category of intensity, its features and means of expression in language and speech have attracted the attention of many scientists in recent decades. This is due to a number of reasons. The category of intensity has the property of universality: characterizing actions, objects and signs, it actively manifests itself in the semantic structure of verbs, nouns, adjectives, adverbs, phraseological units and an integral text. The structure of this category is directly determined by such basic philosophical categories as quality, quantity, measure.